Exploring the effect of valproic acid levels on patients with epilepsy treated with ketogenic diet: An observational study - Stacey Tarrant; Aurelija Liubauske; Guangyu Zhu; Bo Zhang; Heidi Pfeifer; Ann Paris; Ann M. Bergin; Anna L. Pinto (Epilepsia Open)
Abstract Ketogenic diet (KD) therapy is an effective treatment for children with refractory epilepsy. Concurrent treatment with KD and valproic acid (VPA) has previously been shown to affect VPA blood levels. The aim of this study was to explore how VPA levels affect beta‐hydroxybutyrate (BHB) levels of children treated with both. We identified 36 children <18 years old concurrently treated with VPA and classic KD between 2018 and 2022. Retrospective data collected from the medical record: date of birth, sex, feeding method, diet initiation and discontinuance dates, VPA initiation and discontinuance dates; and serial weights, KD ratios, levocarnitine dosages, VPA dosages, and BHB, free carnitine, and VPA levels. Repeated‐measure data was assessed using univariate and multivariate linear mixed‐effects regression analysis. Results showed a statistically significant negative association between VPA and BHB levels based on a univariate LME regression analysis. Conversely, for each 1 mmol/L increase in BHB level, VPA level decreased by 6.39 μg/mL (p < 0.001). Our study indicates that VPA and BHB levels should be monitored closely for children on both treatments and treatment plans may need adjusting if seizure control is not achieved. Plain Language Summary This study focuses on children with epilepsy treated with both the ketogenic diet and VPA. It shows that as levels of VPA increase, blood ketone levels decrease, and vice versa. These results suggest that doctors should closely monitor these levels and potentially adjust treatment plans for children on both therapies if seizures are not well controlled.